Chemical composition of wet, bulk, and dry deposition in kirklareli, Turkey - (:unkn) unknown (My University, 2013)
This study presents that wet, bulk, and dry deposition types were investigated simultaneously in two areas in the Kirklareli city center and Kirklareli rural area in the period of June 2011 - September 2011. The rural area is located 3 km southwest of Kirklareli. During the study period, 8 wet, 8 bulk, and 12 dry samples were collected simultaneously in both sampling areas. The samples were analyzed for Na+, Mg2+, Ca2+, K+, NH4+, Cl-, NO3- and SO42- in addition to pH and altogether 252 analysis were carried out. This paper presents a comparison between wet, bulk, and dry deposition concentrations of ions in the urban and the rural areas. Mg2+ was found to be the dominant cation for wet and bulk depositions in both sampling areas. The pH values of the wet deposition in the urban area varied from 6.04 to 6.75. The arithmetic mean concentrations of ions sampled in the rural area in the wet deposition were 17-75% higher than that of the urban area. © SGEM2013 All Rights Reserved by the International Multidisciplinary Scientific GeoConference SGEM.
Keywords: Ion concentration; Rural area; Urban area